Some Features of Freezing of Halophilic Microalgae by Example of Dunaliella salina Teod. - Chernobai, Nadiia A.; Kadnikova, Natalia G. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 156